INSTITUTIONAL TRANSFORMATION AND COMPETITIVENESS OF SMALL INDUSTRIAL ENTERPRISES: THE CASE OF KHOREZM REGION (Marketing Jurnali, 2025)
The article analyzes the main trends of small business participation in industrial production processes, using the Khorezm region as a case study. Based on statistical data, the study examines the volume of industrial output produced by small enterprises in recent years, growth rates, and structural characteristics. The regional analysis identifies the share of small business in industry, its activity in leading sectors, and its impact on production efficiency, as well as the interrelation with investment processes. Furthermore, the opportunities and existing challenges of small business development in industry are assessed, and practical recommendations for their improvement are proposed.